The electrocardiogram in hypertensive patients. P wave dispersion: a new measure to be considered - Elibet Chávez González; Emilio González Rodríguez; Jesús Castro Hevia; María Del Carmen Llanes Camacho; Yosvany García Nóbrega; Raimundo Carmona Puerta; Ramiro Ramos Ramírez (Medisur)
The electrocardiogram is a complementary test with high specificity but low sensitivity. In the case of patients with arterial hypertension it is of great importance in the diagnosis, prognosis and monitoring during treatment. The prevalence of left ventricular hypertrophy observed through electrocardiogram in hypertensive patients has been reported in up to 9% of them. Different indexes have been described to approach the diagnosis of left ventricular hypertrophy, including the Sokolow and Cornell indexes. Atrial and ventricular arrhythmias are both considered as comorbidity in arterial hypertension. The mechanisms involved are varied and include left ventricular hypertrophy and myocardial ischemia. In patients suffering from hypertension, premature atrial complexes are frequently found and there is an increasing risk of atrial fibrillation, mainly in patients over 65 years old. The predisposition of patients with hypertension to episodes of paroxysmal atrial fibrillation can be determined through manual measurement of P wave’s maximum, minimum and dispersion. The highest values of P wave dispersion in the reading of a 12-lead surface electrocardiogram are more related to events of paroxysmal atrial fibrillation. Irrigation increases in patients with P wave maximum values up to 134 ms and P wave dispersion values up to 46 ms.